Biotransformation and Cytotoxicity Evaluation of Kraft Lignin Degraded by Ligninolytic Serratia liquefaciens - Singh, Anil Kumar; Yadav, Pooja; Bharagava, Ram Naresh; Saratale, Ganesh Dattatraya; Raj, Abhay (Frontiers in Microbiology, 2019)
Various chemical compounds emerged including kraft lignin during the processes of papermaking. These chemical compounds in effluent of the paper industry have hazardous environmental impacts. Kraft lignin is liable for causing pollution of aquatic and water bodies hence; it must be minimized in order to maintain a healthy and sustainable environment. In the present study, kraft lignin degradation was performed with ligninolytic bacterium Serratia liquefaciens and we confirm biotransformation of kraft lignin to various less polluted or harmless compounds. Kraft lignin being degraded as 1000 mg/L-1 concentration with incubating 30°C for 72, 168, and 240 h, shaking at 120 rpm under laboratory conditions. We found 65% maximum degradation of kraft lignin and 62% decolonization by the treatment with Serratia liquefaciens for 240 h (10 days). After being the treatment of kraft lignin, clear changes were observed in its morphology (using scanning electron microscopy and stereo microscopy), hydrodynamic size (using dynamic light scattering), and the functional groups (using attenuated total reflectance–Fourier transform infrared [ATR–FTIR] spectroscopy). Biotransformation of Kraft lignin monitored by Gas chromatography-mass spectrometry (GC-MS) revealed formation of various metabolites. In addition to degradation of kraft lignin, detoxification (involving biotransformation into various metabolites) was assessed using cytotoxicity assays (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide ([MTT] assays and calcein-acetoxymethyl [AM] assays) using a human kidney cell line (NRK-52E), which indicated improved cell survival rates (74% for the bacteria-treated KL solution treated for 240 h) compared to the control (27%). Thus, the present study suggests that, bacteria Serratia liquefaciens might be useful in reducing the pollution of kraftlignin by transforming it into various metabolites along with cytotoxicity reduction for environmental protection.